RCM modeling of bubble injections into the inner magnetosphere: geosynchronous orbit and the ionospheric responses - Sadeghzadeh, Sina; Yang, Jian; Toffoletto, Frank; Wolf, Richard; Mousavi, Ameneh; Wang, Chih-Ping (Frontiers in Astronomy and Space Sciences, 2023)
Introduction: Accurate characterization of the plasma sheet source population in the ring current region and its outer boundary at geosynchronous orbit is crucial for understanding the dynamics of the Earth’s magnetosphere. The interaction between the ring current and plasma populations from the ionosphere is a focus of extensive research. Methods: We used the Rice Convection Model (RCM) to simulate the transient meso-scale injections of fast flows or plasma sheet bubbles from the outer boundary into the inner magnetosphere and the associated impacts on the ionosphere. We compared our simulation results of the average properties of bulk plasma access to geosynchronous orbit to a number of empirical models. We also examined the role of plasma sheet bubbles in forming field-aligned currents (FACs). Results: Our modeling results show that impulsive plasma sheet injections dramatically alter the average distribution of FACs in the ionosphere. We found both quantitative and qualitative agreements and disagreements when comparing our simulation results to empirical models. Furthermore, we demonstrated that several discrete auroral structures can be identified in the nightside ionosphere in accordance with theupward FACs. Discussion: The significance of plasma sheet bubbles in modifying the averageplasma properties at geosynchronous orbit and FACs in the ionosphere is highlighted by oursimulation findings, offering novel understandings into the dynamics of Earth's magnetosphere,and emphasizing the necessity for further research in this field.